2012
DOI: 10.1186/1754-6834-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Value-added uses for crude glycerol--a byproduct of biodiesel production

Abstract: Biodiesel is a promising alternative, and renewable, fuel. As its production increases, so does production of the principle co-product, crude glycerol. The effective utilization of crude glycerol will contribute to the viability of biodiesel. In this review, composition and quality factors of crude glycerol are discussed. The value-added utilization opportunities of crude glycerol are reviewed. The majority of crude glycerol is used as feedstock for production of other value-added chemicals, followed by animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
504
0
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(557 citation statements)
references
References 82 publications
6
504
0
18
Order By: Relevance
“…Supplementing poultry feed with glycerin is also justified because dietary glycerin has a high absorption rate (Yang et al 2012), because glycerin is absorbed both by active and passive processes in the intestine (Kato et al 2004;Ohta et al 2006), and is converted into an energy source through multiple metabolic processes. Several authors have shown that up to 5% glycerin can be included in broiler chicken diets (Cerrate et al 2006;Kroupa et al 2011; al.…”
Section: Mixed Crude Glycerin In Laying Hen Diets: Live Performance Amentioning
confidence: 99%
“…Supplementing poultry feed with glycerin is also justified because dietary glycerin has a high absorption rate (Yang et al 2012), because glycerin is absorbed both by active and passive processes in the intestine (Kato et al 2004;Ohta et al 2006), and is converted into an energy source through multiple metabolic processes. Several authors have shown that up to 5% glycerin can be included in broiler chicken diets (Cerrate et al 2006;Kroupa et al 2011; al.…”
Section: Mixed Crude Glycerin In Laying Hen Diets: Live Performance Amentioning
confidence: 99%
“…Teóricamente puede obtenerse 0,1 l de glicerol por cada litro de biodiesel, además de metanol y agua (Singhabhandhu y Tezuka, 2010;Chatzifragkou et al, 2011). La glicerina es empleada en la industria alimentaria y farmacéutica bajo los estándares USP (United States Pharmacopeia) y FCC (Food Chemicals Codex); en la producción de dinamita (Rincón y Martínez, 2009;Posada-Duque y Cardona-Alzate, 2010), cosméticos, pintura, pulpa, papel, cuero y textiles (Pagliaro y Rossi, 2008;Singhabhandhu y Tezuka, 2010;Chatzifragkou et al, 2011); como sustrato para la producción de metabolitos, tales como los ácidos orgánicos, 1,3-propanodiol, ácido cítrico, polioles y lípidos (Yazdani y Gonzalez, 2007;Chatzifragkou et al, 2011), en la dieta de rumiantes y algunos otros animales (Yang et al, 2012), y en la producción de etanol combustible, utilizando cepas de Escherichia coli (Posada y Cardona, 2010) …”
Section: Glicerolunclassified
“…These additions help animals to gain weight through efficient feed consumption [137]. It can thus be used to replace corn in animal diet [138]. The other advantages associated with the use of CG are weighed down by presence of impurities, especially methanol [139][140][141].…”
Section: Non-biological Products Animal Foodstuffmentioning
confidence: 99%